A STUDY ON THE STUDENTS' WRITING SKILL OF NARRATIVE TEXT THROUGH PICTURES SERIES AT X GRADE OF MAN 3 INDRAGIRI HILIR - Rozitah; Agus Mustajib; Maizarah (Program Studi Pendidikan Bahasa Inggris, 2026)
Writing is the process of producing written expressions or sentences to communicate thoughts or emotions using symbols. Narrative text refers to a type of writing that presents a story in a structured and chronological order, which can be based on either fictional or real-life events. This study aims to assess students’ ability in writing narrative texts using a sequence of pictures. The researcher employed a descriptive research method to analyze the data, using a writing test as the primary instrument for data collection. The research population consisted of all 10th-grade students, and the sample was selected through random sampling, involving 10 students from each class. The findings indicated that the average score for students’ writing ability was 79.56, which falls under the “fair” category. In conclusion, students’ writing proficiency was considered moderately good in aspects such as content, organization, language use, and writing mechanics.